An in-bath liquidus measurement for molten salts and slags - Grimsey, Eric; Li, N.; Yan, Y.; Warczok, A.; Utigard, T.A. (1996)
A technique is being developed to provide a rapid in-bath measurement of the liquidus temperature for salts and metallurgical slags. A copper or nickel cylinder is immersed into a molten bath and a computer based data-logging system is used to record the heating profile of a type K thermocouple centered within the cylinder. The heat transfer is affected initially by the presence of a thin crust on the cylinder surface which freezes from the bath. When the crust melts, the rate of heating shows a subtle increase. Numerical differentiation is used to detect the on-set of this increase so as to provide an indication of the liquidus temperature of the melt. This paper outlines the technique predominantly through measurements of the melting points of pure sodium chloride and sodium nitrate. Factors which may affect the sensitivity of the measurement are discussed also.